EVALUASI PROGRAM KESEJAHTERAAN SOSIAL ANAK BALITA (PKSAB) DI KOTA SEMARANG - Nike Triana; Hartuti Purnaweni; Dyah Hariani (Journal of Public Policy and Management Review, 2013)
Population growth is moving very fast while not accompanied by increasing sum of jobs will lead to poverty. When poverty struck people, the most visible result is a decrease in the welfare of the child is obtained, in line with the decline their parents welfare. To overcome these problems, through the activities of Deconcentration fund for Rehabilitation and Social Protection, Ministry of Social Affairs through Central Java Social Provincial office, implement toddler social welfare programs in Semarang City (PKSAB) to meet their basic needs. The purpose of this study to determine the implementation PKSAB in Semarang and factors inhibiting and supporting implementation of PKSAB.Theory used is the evaluation theories of William Dunn, James Anderson, Thomas R Dye, Riant Nugroho and Samudra Wibawa. This study used qualitative methods with 8 people as informants. Data collection techniques were observation and interview, in which the data were processed and analyzed qualitatively.The result indicate that PKSAB effective accordance with the procedures. The program is managed in accordance with the indicators of program better fulfill meet the toddler need, improve the child in meeting basic needs, improving accessibility to basic social services, strengthening parental responsibility and institutional strengthening. Inhibiting factor program is the responsibility of parents, parents less conscious of the importance of education for toddler, toddler growth monitoring is neglected, and the parents have not been able to meet the toddler basic needs. Recommendations for PKSAB in Semarang is strengthening the Social Workers knowledge on PKSAB, the clarity of the main tasks given to Social Workers, as well as participation of Social Service of Semarang office.